A Dynamic Process Model of Service Quality: From Expectations to Behavioral Intentions - Boulding, William; Kalra, Ajay; Staelin, Richard; Zeithaml, Valarie A. (Journal of Marketing Research, 1993)
Relying on a Bayesian-like framework, the authors develop a behavioral process model of perceived service quality. Perceptions of the dimensions of service quality are viewed to be a function of a customer's prior expectations of what will and what should transpire during a service encounter, as well as the customer's most recent contact with the service delivery system. These perceptions of quality dimensions form the basis for a person's overall quality perception, which in turn predicts the person's intended behaviors. The authors first test this model with data from a longitudinal laboratory experiment. Then they develop a method for estimating the model with one-time survey data, and reestimate the model using such data collected in a field study. Empirical findings from the two tests of the model indicate, among other things, that the two different types of expectations have opposing effects on perceptions of service quality and that service quality perceptions positively affect intended behaviors.